[OP.7A.05] TRENDS IN PREVALENCE, TREATMENT AND CONTROL OF HYPERTENSION IN CROATIAN CONTINENTAL RURAL POPULATION - ENAH STUDY. (September 2016) - Vrdoljak, A.; Ivkovic, V.; Karanovic, S.; Dika, Z.; Domislovic, V.; Dapic, K.; Gallineo, L.; Ivandic, E.; Josipovic, J.; Vukovic, I.; Kos, J.; Laganovic, M.; et al.
Abstract : Objective: Overall prevalence of hypertension (HT) in Croatia is high and control of HT is poor. In this study our aim was to analyze trends in prevalence, treatment and control of HT in the same rural population during the 10 years long survey. Design and method: Out of 3056 subjects enrolled in ENAH study, 2361 were eligible for further analysis. All inhabitants older than 18 years of age from this rural area were invited to participate and were examined on a door-to-door basis. Pregnant women, patients with terminal illness who were bed-ridden, patients with severe disability or those who have had at least one limb amputated or immobilized and mentally ill or suffering from dementia were considered ineligible. Participation rate was >70%. Blood pressure (BP) and heart rate (HR) were measured using Omron 6 device following the ESH guidelines. HT was defined as a BP > = 140/90 mmHg, and/or current use of antihypertensive drugs. Treatment of HT was defined as usage of antihypertensive medication at the time of the interview. Control of treated HT was defined as BP < 140/90 mmHg. Villagers were examined in 2005, 2008, 2010 and 2015, and trends of prevalence, treatment and control were analysed. There were no differences in age and gender among various years groups. Results: Prevalence of HT decreased from 2005 to 2010 but still remains very high (64.1% vs. 55.2%; p = 0.04). Prevalence of treated HT significantly increased from 2005 to 2015 (26.8% vs. 68.5%; p = 0.001). Prevalence of controlled HT gradually increased and in 2005, 2008, 2010 and 2015 was 11.%, 14.5%, 15.1% and 17.3%, respectively; p = 0.09). Significant decrease in average systolic BP was observed (p for trend <0.001 for systolic BP). Conclusions: Prevalence of HT in Croatian rural area remains very high. Nowadays, much more HT were treated and there is trend to better control. However, results are still unacceptable. High salt consumption, obesity, poor socioeconomic status and low educational level are the most import causes of such thrashing result.